The Impact Of Organizational Culture On The Performance Of Civil Servants (A Study At The Regional Planning, Research, And Development Agency Of Bengkulu Province) - Apriani, Insira; Saputra, Harius Eko; Handayani, Tuti (Journal of Multidisciplinary Research, 2025)
This research aims to determine the impact of organizational culture on the performance of Civil Servants (PNS) at the Regional Planning, Research, and Development Agency of Bengkulu Province. The method used in this study is a quantitative descriptive method. Data collection techniques were conducted through the distribution of questionnaires to 84 respondents as research samples. The obtained data were analyzed using simple linear regression. The analysis results show that the regression equation obtained is Y = 7.763 + 0.997X, indicating a positive relationship between organizational culture (X) and employee performance (Y). The correlation value (R) of 0.758 indicates a strong relationship between the two variables, and the coefficient of determination (R²) of 0.575 indicates that 57.5% of the variation in employee performance can be explained by organizational culture. The t-test produced a significance value of 0.000, which is less than α = 0.05, concluding that organizational culture significantly affects the performance of Civil Servants in that institution. Thus, improving organizational culture can encourage an increase in employee performance.